The effect of Zn doping concentration on thermoelectric properties of CuAgSe - Nguyen, Thi Huong; Nguyen, Van Quang; Phan Nguyen Duc, Duoc; Cho, Sunglae; Phan, Van Cuong (Vietnam Journal of Science and Technology, 2025)
CuAgSe is a potential thermoelectric material with high carrier mobility and ultralow lattice thermal conductivity. In this study, to improve the thermoelectric properties of CuAgSe, Zn was doped at different ratios (x = 0, 0.02, 0.04, 0.06, 0.08, and 0.10) into Cu sites as the formula Cu1-xZnxAgSe. Zn-doping CuAgSe polycrystals were successfully fabricated by growth from the melt method. The crystal structure of CuAgSe samples was investigated by XRD. The effect of Zn-doping on the thermoelectric properties of CuAgSe samples was studied in the temperature range from 300 – 673 K. When doping Zn into CuAgSe samples, the lattice thermal conductivity reduces to about 0.3 W m-1 K-1 at 673 K and increases the electrical conductivity compared to undoped CuAgSe. Interestingly, the highest ZT value of  Cu0.94Zn0.06AgSe is about 0.69 at 673 K, 3.5 times compared to undoped CuAgSe.